Firm Profitability and Adjustment of Capital Structure: Indian Evidence. Issue 3 (September 2019) - Ghose, Biswajit; Kabra, Kailash Chandra
The present study investigates the relevance of capital structure dynamics in Indian context by examining the speed at which firms adjust towards their target capital structure. Apart from symmetric adjustment speed, the study also investigates the asymmetries in adjustment speed based on profitability of firms. Using partial adjustment framework on an unbalanced panel of 28, 532 firm-year observations comprising 2, 718 listed firms over a period of 2004–2005 to 2015–2016, the study finds that Indian firms maintain target leverage and adjust towards the same with a moderate annual adjustment speed of around 32 per cent. The study further observes that high-profitability firms, in general, adjust significantly faster than low-profitability firms which possibly indicate better accessibility in the financial market, lesser costs of adjustments and ability to adjust payout ratio for the former than the latter. Further investigation reveals that high-profitability firms make more adjustment in case of over-leverage, whereas low-profitability firms make more adjustment in case of under-leverage. These results possibly indicate the implications of availability of internally generated funds. Overall, the study concludes that adverse selection cost plays important role in the target adjustment process and hence, both trade-off theory and pecking order theory have relevance in Indian context.